Adaptation and Effect of Virtual Reality Application on Interior Architecture Profession - Kömürcü, Tuğba; Kavut, İsmail Emre (Journal of Interior Design and Academy, 2024)
Digital design projects and the advancement of technology affect the field of interior architecture as it affects all design fields. The error rates of the projects presented with traditional methods and customer satisfaction have decreased. With the advancement of technology, designers looking for different presentation styles and practical solutions have entered new searches. Virtual reality has started to be used in the field of interior architecture as it is used in health, entertainment and many similar fields. For this reason, it is seen that virtual reality is used in project presentations in architecture, interior architecture and other fields to make the design qualified and gain speed. This article focuses on the benefits of virtual reality technology in design processes. Problems such as the inability to express the design directly and the inability to achieve the expected physical results are minimized thanks to virtual reality. The project aims to increase customer satisfaction and save time and cost by experiencing elements such as color, proportion, texture and material control in a virtual environment. Virtual reality allows visualization of the design, helping users to better understand the project and identify potential problems at an early stage.